Pregnancy Exercise Counseling and Assistance to Reduce Discomfort During Pregnancy - Wulan, Sri; Putri, Dea Febriana; Junia, Rita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Pregnancy is a time full of physical and emotional changes, which are often accompanied by various discomforts. One effort to reduce this discomfort is through pregnancy exercise, which has been proven to provide both physical and psychological benefits. This community service aims to explore the impact of pregnancy exercise counseling and assistance in reducing discomfort during pregnancy. This activity was carried out on November 5 2024 at the Matahari Clinic Tanjung Morawa involving 14 pregnant women who underwent ANC visits. Through counseling about pregnancy exercise and practical assistance, pregnant women are given an understanding of the benefits of pregnancy exercise in reducing physical complaints such as back pain and leg cramps, as well as reducing anxiety that is often experienced during pregnancy. The results of the activity showed that pregnant women who participated felt calmer and had better physical readiness before giving birth. Thus, counseling and assistance with pregnancy exercise can be an effective method in improving the well-being of pregnant women, both physically and psychologically, during pregnancy.